Filamentous Fungi and Mycotoxins in Cheese: A Review. Issue 4 (July 2014) - Hymery, Nolwenn; Vasseur, Valérie; Coton, Monika; Mounier, Jérôme; Jany, Jean‐Luc; Barbier, Georges; Coton, Emmanuel
Abstract Important fungi growing on cheese include Penicillium, Aspergillus, Cladosporium, Geotrichum, Mucor, and Trichoderma. For some cheeses, such as Camembert, Roquefort, molds are intentionally added. However, some contaminating or technological fungal species have the potential to produce undesirable metabolites such as mycotoxins. The most hazardous mycotoxins found in cheese, ochratoxin A and aflatoxin M1, are produced by unwanted fungal species either via direct cheese contamination or indirect milk contamination (animal feed contamination), respectively. To date, no human food poisoning cases have been associated with contaminated cheese consumption. However, although some studies state that cheese is an unfavorable matrix for mycotoxin production; these metabolites are actually detected in cheeses at various concentrations. In this context, questions can be raised concerning mycotoxin production in cheese, the biotic and abiotic factors influence their production, mycotoxin relative toxicity as well as the methods used for detection and quantification. This review emphasizes future challenges that need to be addressed by the scientific community, fungal culture manufacturers, and artisanal and industrial cheese producers.